Visual Outcome and Complications of 23 G Versus 20 G Vitrectomy in Cases of Diabetic Vitreous Haemorrhage - Syed Fawad Rizvi, Syed Asad Mahmood, Washoo Mal, Shakir Zafar, Zafar Iqbal (Pakistan Journal of Ophthalmology, 2014)
Purpose: To compare post-operative visual outcome and complications of 23-gauge versus 20-gauge pars plana vitrectomy in cases of vitreous haemorrhage secondary to proliferative diabetic retinopathy. Material and Methods: Randomized clinical trial conducted at LRBT, Free Base Eye Hospital, Karachi, from January 2010 to June 2012. Two hundred sixty patients of vitreous haemorrhage secondary to proliferative diabetic retinopathy (Type – l diabetes mellitus) were randomly selected, age range between 30 – 70 years, 23 – gauge (n = 130) group A; males 73 (56.16%), females 57 (43.85%) and 20 – gauge pars plana vitrectomy (n = 130) group B; males 70 (53.85%), females 60 (46.15%). Post-operative follow up were at day one, 1 week, 1 month, 2 month, 3 month and final 6 month. Data was analyzed and compared for post-operative best corrected visual acuity (BCVA) and complications between two groups. Results: Visual acuity significantly improved in majority of patients in both groups. In group A 65.38% (85 patients) achieved between 6/6 - 6/24 and in group B 63.85% (83 patients) in same range when measured finally at 6 month post-operative. Post operative complications in group A were transient hypotony 10.77% (14 eyes), recurrent vitreous haemorrhage 6.15% (8 eyes), raised IOP 3.08% (4 eyes), Cataract 3.84% (5 eyes), Itrogenic tear 9.23% (12 eyes), vitreous show (prolapsed) 3.84% (5 eyes) and 1 patient (0.76%) developed endophthalmitis which was treated successfully. While in group B transient hypotony 6.15% (8 eyes), recurrent vitreous haemorrhage 18.46% (24 eyes), raised IOP 7.69% (10 eyes), Cataract 3.84% (5 eyes), Itrogenic tear 7.69% (10 eyes) and phthisis bulbus 0.76% (1 eye), corneal edema 6.92% (9 eyes), and conjunctival granuloma at surgical wound 2.30% (3 eyes) observed. Conclusion: 23 – gauge micro-incision Vitrectomy system MIVS and 20-gauge pars plana vitrectomy showed improvement in best corrected visual acuity (BCVA) while early visual recovery and less complications rate seen in patients of 23 – gauge group. Key words: Vitrectomy, Diabetic retinopathy, Vitreous haemorrhage.